ANALISIS PENERAPAN PP 23 TAHUN 2018 PADA WAJIB PAJAK UMKM (STUDI DI KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR UTARA) - AM, Memi Pratiwi; Nasaruddin, Fadliah; Alam, Syamsu (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
The purpose of this re search is to analze identify application PP No. 23 Year 2018 on Taxpayer MSMEs on Tax Service Office Pratama North Makassar.The data required in this study is primary data and secondary data. Data collection methods used in this study is the interview and documentary. Data analysis techniques used by kualitative analysis. The results showed that the implementation of PP No. 23 Year 2018 on Taxpayer MSMEs on Tax Service Office Pratama North Makassar has been going well and is in accordance with the principles of tax collection. The lowered tax rate to 0.5%, cheap tax administration and easy deposit procedures illustrate the implementation of the principles of equality, certainty, convenience and economy.Keyword: PP No. 23 Year 2018, Taxpayer, MSMEs